Risk assessments of lumpy skin diseases in Borena bull market chain and its implication for livelihoods and international trade - Alemayehu, Gezahegn (Springer Netherlands, 2012)
Risks of introduction of lumpy skin disease (LSD) through traded Borena bulls to market chain and its consequences were assessed. The assessment used the framework that has been recommended by the World Animal Health Organization (OIE) for risk analysis. Likelihoods for release and exposure were estimated by a qualitative scale ranging from negligible to very high, whereas the consequences which resulted from disease occurrences were assessed quantitatively. The likelihood of the introduction of LSD to the market chain through traded Borena bulls is found to be high (medium uncertainty), whereas the probability of exposure is very high (medium uncertainty). From the total of 11,189 bulls observed during outbreak investigation of LSD in six sites of feedlot operation in and around Adama, 681(6.1 %) and 204 (1.8 %) bulls were found to be affected and dead with LSD, respectively. The total economic loss due to LSD was estimated to be 667,785.6 USD. The risk estimates for LSD are greater than negligible; therefore, disease prevention and control strategy along the chain should be carefully considered by the Ethiopian veterinary services.